Improved pulse wave velocity and renal function in individualized calcineurin inhibitor treatment by immunomonitoring: the randomized controlled calcineurin inhibitor-sparing trial - Sommerer, Claudia; Brocke, Janina; Bruckner, Thomas; Schaier, Matthias; Morath, Christian; Meuer, Stefan; Zeier, Martin; Giese, Thomas (Transplantation, 2018)
BACKGROUND: A new immune monitoring tool which assesses the expression of nuclear factor of activated T cells (NFAT)-regulated genes measures the functional effects of cyclosporine A. This is the first prospective randomized controlled study to compare standard pharmacokinetic monitoring by cyclosporine trough levels to NFAT-regulated gene expression (NFAT-RE). - METHODS: Expression of the NFAT-regulated genes was determined by qRT-PCR at cyclosporine trough and peak level. Cardiovascular risk was assessed by change of pulse wave velocity from baseline to month 6. Clinical follow-up was 12 months. - RESULTS: In total, 55 stable kidney allograft recipients were enrolled. Mean baseline residual NFAT-RE was 13.1 ± 9.1%. Patients in the NFAT-RE group showed a significant decline in pulse wave velocity from baseline to month 6 versus the standard group (-1.7 ± 2.0 m/s vs 0.4 ± 1.4 m/s, P < 0.001). Infections occurred more often in the standard group compared with the immune monitoring group. No opportunistic infections occurred with NFAT-RE monitoring. At 12 months of follow-up, renal function was significantly better with NFAT-RE versus standard monitoring (Nankivell glomerular filtration rate: 68.5 ± 17.4 mL/min vs 57.2 ± 19.0 mL/min; P = 0.009). - CONCLUSIONS: NFAT-RE as translational immune monitoring tool proved efficacious and safe in individualizing cyclosporine therapy, with the opportunity to reduce the cardiovascular risk and improve long-term renal allograft function.